2020
DOI: 10.1007/s12518-020-00322-7
|View full text |Cite
|
Sign up to set email alerts
|

Categorisation of building data in the digital documentation of heritage buildings

Abstract: The documentation of heritage buildings is the preliminary action to deal with any problem related to the built heritage. The procedure of documentation requires a very diverse range of data (quantitative and qualitative) to be obtained and investigated in order to produce an accurate digital representation of the building. This type of work of data capture and interpretation is often conducted in isolation by different stakeholders and for a range of purposes, leading to a lack of communication between differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 41 publications
2
29
0
2
Order By: Relevance
“…As HBIM practical cases show, the initial study of the historical contextualization of the building, the study of materials and analysis of construction processes are important. The importance of the methodology of information collection, standardization, construction techniques, the use of scanners, virtual reality and photogrammetry is reported in our study and has already been reported in previous reviews up to 2019 [31][32][33][34][35][36][37][38] and 2020 [39]. Studies focusing on linked open data (LOD) [40], digital documentation of heritage buildings [37] and performance assessment in HBIM [41] remain areas of interest.…”
supporting
confidence: 53%
“…As HBIM practical cases show, the initial study of the historical contextualization of the building, the study of materials and analysis of construction processes are important. The importance of the methodology of information collection, standardization, construction techniques, the use of scanners, virtual reality and photogrammetry is reported in our study and has already been reported in previous reviews up to 2019 [31][32][33][34][35][36][37][38] and 2020 [39]. Studies focusing on linked open data (LOD) [40], digital documentation of heritage buildings [37] and performance assessment in HBIM [41] remain areas of interest.…”
supporting
confidence: 53%
“…In the heritage buildings sector, challenges of longevity are even greater as -alongside the preservation of the building itself -the digital data of the building should also be preserved and accessed for a longer time to act as a record of the building and its alterations over its lifespans (Khalil, Stravoravdis, and Backes 2020). In fact, the data of the building should ideally outlive the building itself, to serve as an accurate representation and documentation of the building in case of any loss or damage of the building's fabric.…”
Section: Related Workmentioning
confidence: 99%
“…This is shortly followed by the development of 3D visualisation software. The introduction of BIM (Building Information Modelling) tools further developed the ways of architectural representation in that it introduced an environment that can link several forms of buildings digital representation such as 2D drawings, 3D models, parametric information, photographic representation, and many other forms of data (Khalil, Stravoravdis, & Backes, 2020). Later, the introduction of extended reality applications and their rapid development paved the way towards a new era of immersive and interactive visual communication.…”
Section: Background On Historical Building Representationmentioning
confidence: 99%
“…HBIM tools represent a crucial development in the heritage buildings sector. It facilitates the integration of different stakeholders into a unified platform that can combine the various data about heritage buildings (Khalil, Stravoravdis, & Backes, 2020). HBIM can incorporate both quantitative assets (intelligent objects, performance data) and qualitative assets (historic photographs, oral histories, music) (Fai, Graham, Duckworth, Wood, & Attar, 2011), as well as historic texts, archaeological figures, architectural information, administrative data and past drawings, sketches, photos, etc.…”
Section: H-bim and Extended Reality In Heritage Buildings Representationmentioning
confidence: 99%